LAW No. 10,639/2003 AND THE IMPLEMENTATION OF EDUCATION FOR ETHNIC-RACIAL RELATIONS IN BASIC EDUCATION : Law nº. 10,639/2003 and the implementation of education for ethnic-racial relations in basic education - Ferreira da Costa, Márcia (2024)
This study aims to present Law 10.639/2003, highlighting the importance of its contribution to the implementation of an anti-racist education in our high schools. Bibliographical and documentary research was used as methodology. It relied on Almeida e Medeiros (2007), Gomes e Jesus (2013), Barreto (2016), Almeida e Sanchez (2017),  Ribeiro (2019), Landim e Saraiva (2020) and Santos (2022),  for the construction of the theoretical foundation about the contribution of the presented normative. We found that the evidence of traditional practices arising from a eurocentric education and the consequent invizibilization of black culture is a reflection of gaps in relation to the failure to comply with the implementation of Law 10,639/2003, and that it is necessary to reconstruct the pedagogical practice from the knowledge of the normative in question and its guidelines,  so that the practice in the school environment is consistent with the determinations of the aforementioned Law and the fight against structural racism.